2017
DOI: 10.17116/patol201779319-26
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanisms and morphological manifestations of leiomyoma reduction induced by selective progesterone receptor modulators

Abstract: The molecular mechanisms of tumor reduction involved the reduced Ki-67 expression and elevated p16, lower VEGF and TGF-β, diminished SRC-1 expression with the maintained level of PR, ER, and NCoR-1. Overall, this is suggestive of enhanced apoptosis and reduced leiomyoma proliferation and angiogenesis induced by SPRM and indicative of the expediency of using ulipristal acetate as a preoperative agent for organ-sparing surgery in reproductive-aged patients with uterine myoma, menorrhagias, and anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…To date, data on the effects of SPRM on the expression of estrogen and progesterone receptors in myomas remain scanty and somewhat ambiguous. In 2017, Demura et al—in addition to increased apoptosis and reduced leiomyoma proliferation and angiogenesis induced by UPA—noted no effect on the expression of PRs and ERs in myoma tissue [ 23 ]. Tinelli et al [ 24 ], in their study on the effects of UPA treatment on myomas ex vivo, noticed significant differences in the expression patterns of proteins related to regulation of the cell cycle, remodeling of the cell cytoskeleton and also drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To date, data on the effects of SPRM on the expression of estrogen and progesterone receptors in myomas remain scanty and somewhat ambiguous. In 2017, Demura et al—in addition to increased apoptosis and reduced leiomyoma proliferation and angiogenesis induced by UPA—noted no effect on the expression of PRs and ERs in myoma tissue [ 23 ]. Tinelli et al [ 24 ], in their study on the effects of UPA treatment on myomas ex vivo, noticed significant differences in the expression patterns of proteins related to regulation of the cell cycle, remodeling of the cell cytoskeleton and also drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also suggested that simultaneous evaluation of the clinical-pathological markers such as tumor size, mitotic index, and IHC Ki-67, Bcl-2 greatly increases statistical significance ( p = 0.001) [75]. Recently, Demura et al (2017), reported lower Ki-67 expression in those patients treated with selective progesterone receptor modulators (SPRMs) whose tumor volume significantly decreased, and claimed it was an antiproliferative and a proapoptotic effect of the treatment [32].…”
Section: Available Immunohistochemical Markersmentioning
confidence: 99%
“…(a) proteins that control the cell cycle and have a direct influence on the dynamics of proliferation, e.g., p16 [32,33,34]; cyclin D1 [35,36]; Bcl-2 [37]; proliferating cell nuclear antigen (PCNA) [38];…”
Section: Introductionmentioning
confidence: 99%
“…25 , 26 More recently, UPA was shown to impact cell proliferation and angiogenesis by decreasing Ki-67 activity and reducing expression of vascular endothelial growth factor. 27 Ulipristal acetate has been compared to other therapeutic approaches, evaluated for presurgical administration, and has shown considerable effectiveness when used long term in patients with leiomyomas. 23,24,28 Ulipristal acetate negatively impacts collagen deposition, and results in a decrease in the expression of both fibronectin and versican proteoglycan in a randomized controlled study.…”
Section: Introductionmentioning
confidence: 99%